2006
DOI: 10.1002/biot.200600143
|View full text |Cite
|
Sign up to set email alerts
|

Use of virus vectors for the expression in plants of active full‐length and single chain anti‐coronavirus antibodies

Abstract: To extend the potential of antibodies and their derivatives to provide passive protection against enteric infections when supplied orally in crude plant extracts, we have expressed both a small immune protein (SIP) and a full-length antibody in plants using two different plant virus vectors based on potato virus X (PVX) and cowpea mosaic virus (CPMV). The alphaSIP molecule consisted of a single chain antibody (scFv) specific for the porcine coronavirus, transmissible gastroenteritis virus (TGEV) linked to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Verch et al . (1998) and Alamillo et al . (2006) used vectors based on tobacco mosaic virus (TMV) and potato virus X (PVX), respectively, and, in each case, infected plants with separate constructs expressing the heavy and light chains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Verch et al . (1998) and Alamillo et al . (2006) used vectors based on tobacco mosaic virus (TMV) and potato virus X (PVX), respectively, and, in each case, infected plants with separate constructs expressing the heavy and light chains.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant drawback when using the natural host of CPMV, cowpea ( Vigna unguiculata ), which possesses a thick cuticle, which must be extensively damaged to allow constructs to be agroinfiltrated into leaves. However, cowpea has the advantage as an expression system that it is an edible plant and has already been used for the expression of HBcAg and SIPs (Alamillo et al ., 2006; Mechtcheriakova et al ., 2006; Monger et al ., 2006). We have recently conducted preliminary experiments on the expression of a human anti‐human immunodeficiency virus (anti‐HIV) IgG in cowpea, which have shown that deleted RNA‐2 molecules can be used to produce assembled antibodies in this host (F. Sainsbury and G. P. Lomonossoff, unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(149). Rapid transient antibody productions in plants has also been performed using modified plant viral vectors (150,151) with production levels of up to 0.7 % of total protein. Monocotyledonous plants are mostly transfected by particle gun (152).…”
Section: Transgenic Plantsmentioning
confidence: 99%
“…The development of plant virus vectors as in planta expression systems for foreign genes provides an attractive alternative biotechnological approach for peptide expression [1][2][3][4][5]. This method has been exploited in vaccine production, where small foreign peptides are expressed as a fusion with the viral coat proteins.…”
Section: Introductionmentioning
confidence: 99%